Pengaruh Strategi Pemasaran Influencer Collaborations, Digital Advertising, Dan Visual Merchandising 3second Terhadap Brand Awareness (Studi Kasus Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Wahyudi, Iqlima Aurelia; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The purpose of this study is to analyze the partial and simultaneous effects on brand awareness of digital advertising, visual merchandise, and influencer collaboration marketing strategy. Using a sample of 90 students from the Islamic University of Malang's 2020 Faculty of Economics and Business class who utilize 3Second goods, a quantitative methodology was employed in the study, out of a total population of 699. A questionnaire was used to gather the data, which was then examined for validity and reliability. The normality, multicollinearity, heteroscedasticity, multiple linear regression analysis, F, R2, and t tests were also performed in this investigation. The findings demonstrated that brand awareness was positively and significantly impacted by influencer cooperation, digital advertising, and visual merchandising all at the same time. To some extent, the three marketing. Keywords: Influencer Collaborations, Digital Advertising, Visual Merchandising, Brand Awareness.